THE EFFECT OF VISUAL AND FUNCTIONAL CRITERIA OF PACKAGING: CONSUMER EXPECTATIONS OF ELEMENTS FOR DAIRY PRODUCT PACKAGING - Farahani, Maryam Ghiasabadi; Shababi, Hooman; Ashtiani, Peyman Ghafari (UI Scholars Hub, 2021)
Manuscript type: Research paper Research Aims: This study seeks to investigate the effect of visual and functional criteria on packaging and consumer expectations towards the packaging elements of dairy products for children. Design/methodology/approach: For this purpose a sample containing 334 children between 7- 12 years were used. Sampling method was random sampling and measuring tool was questionnaire. In order to data analysis and hypothesis testing, structured equations test by means of